PENTINGKAH UMKM MENGHITUNG HARGA POKOK PENJUALAN? - Siti Sarpingah; Angela Dirman (Jurnal Pengabdian Masyarakat Berkelanjutan, 2026)
In determining the selling price, Micro, Small, and Medium Enterprises (MSMEs) often inaccurately include certain cost components beyond raw materials, such as gas, electricity, and labor wages—including compensation for the business owner themselves. Therefore, understanding how to calculate the Cost of Goods Sold (COGS) is essential for MSME actors to set the right selling price for their products or services. This involves calculating all the elements used in the production of goods or services, as well as other supporting variable costs, and then adding a desired profit margin or percentage. This Community Service program was provided to MSME actors in the Kembangan Utara area, focusing on processed products made from purple sweet potatoes as an alternative product for sale. The purpose of this Community Service activity is to educate MSME actors on how to calculate and determine the Cost of Goods Sold (COGS) more accurately. The Outcome of this Community Service were publication on Mass Media, Youtube, and journal publication and HKI.